Sejauhmana Tanggung Jawab Notaris terhadap Surat Dibawah Tangan yang di Daftarkan pada Buku Khusus Notaris (Waarmerking) - Marchellino Fortuna Kano; Khusnul Yaqin (Concept: Journal of Social Humanities and Education, 2024)
In conducting a Notary position, the Notary is required to be able to know the responsibilities and authority of the Notary in performing his/her position in accordance with the Notary Position Law. One of them is the authority of the Notary in Law Number 30 of 2004 concerning the Notary Position jo Law Number 2 of 2014 in Article 15 paragraph 2 letters a and b "Notaries are also authorized: to certify signatures and determine the certainty of the date of letters under hands by registering in a special book; book letters under hands by registering in a special book;" But in the current era, Waarmerking has become a loophole for a Notary to be guilty. Therefore, this research will discuss the extent of the Notary's responsibility for letters under the hand registered in the Notary's special book. This research uses normative legal research methods, data sources come from positive law, laws and books. The results show that in addition to being authorized to make authentic deeds, notaries are also authorized only to register letters under the hands registered in a special book.